2016
DOI: 10.3389/fcell.2016.00144
|View full text |Cite
|
Sign up to set email alerts
|

Nanotopography Induced Human Bone Marrow Mesangiogenic Progenitor Cells (MPCs) to Mesenchymal Stromal Cells (MSCs) Transition

Abstract: Mesangiogenic progenitor cells (MPCs) are a very peculiar population of cells present in the human adult bone marrow, only recently discovered and characterized. Owing to their differentiation potential, MPCs can be considered progenitors for mesenchymal stromal cells (MSCs), and for this reason they potentially represent a promising cell population to apply for skeletal tissue regeneration applications. Here, we evaluate the effects of surface nanotopography on MPCs, considering the possibility that this spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…These nanotopographical features could enhance the spreading behaviour of human MSCs compared to cells on flat control glass surfaces [ 112 ]. Also it has been shown that mesangiogenic progenitor cells (MPCs), which are thought to be progenitors to MSCs, showed differences in spreading/adhesive behaviour when cultured on a 400 nm nanograting topography, compared to a flat control, where more protrusive filopodia were observed on nanograting topography suggesting more spreading potential [ 114 ]. Table 1 summarises several nanotopographical approaches that influence cell adhesion and spreading.…”
Section: Cellular Responses To Nanotopographiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These nanotopographical features could enhance the spreading behaviour of human MSCs compared to cells on flat control glass surfaces [ 112 ]. Also it has been shown that mesangiogenic progenitor cells (MPCs), which are thought to be progenitors to MSCs, showed differences in spreading/adhesive behaviour when cultured on a 400 nm nanograting topography, compared to a flat control, where more protrusive filopodia were observed on nanograting topography suggesting more spreading potential [ 114 ]. Table 1 summarises several nanotopographical approaches that influence cell adhesion and spreading.…”
Section: Cellular Responses To Nanotopographiesmentioning
confidence: 99%
“…Additionally, it has been shown that gold nanorods, fabricated with similar dimensions to the tobacco mosaic virus, enhanced MSC osteogenesis and chondrogenesis when functionalized to hyaluronic acid hydrogels due to the effects of the highly ordered nanotopographical environment [ 122 ]. Differentiation into MSCs from progenitor cells has also been investigated in response to nanotopography where it was shown that MPCs preferentially differentiated into MSCs on a 400 nm nanograting topography than on flat surfaces [ 114 ].…”
Section: Cellular Responses To Nanotopographiesmentioning
confidence: 99%
“…Osteoinductivity is not a merely chemical stimulus. It was demonstrated that material nanotopography can induce MPC-MSC transition as a sole factor; in particular, nanogratings, used as a cell culture substrate, were able to promote cell morphological polarization and stretching, which finally resulted in phenotype change towards the osteogenic lineage [ 152 ]. These results highlighted that some surfaces generate physical stimuli able to address the cells toward specific lineages, thus opening to the interesting possibility of producing nanopatterned biomaterials inherently able to induce stem cell differentiation, without the use of specific growth factors or cell culture media.…”
Section: Piezoelectricity In Bone Tissue Regenerationmentioning
confidence: 99%